(untitled) (Research, Society and Development, 2023)
Objective: to know the perception of nurses in primary health care about the reception of the LGBTQIAP+ population. Methods: this is a descriptive study conducted with nurses working in the Primary Health Care Units (UAPS) of regional 1 of the city of Fortaleza-CE. Eighteen nurses participated through an electronic questionnaire, during the months of November and December 2021. The collected data were analyzed through thematic categorical analysis. Results: two categories emerged that dealt with the concepts and knowledge of primary care nurses about the LGBTQIAP+ population; and the health policy of the LGBT population and the reception in primary care. Some nurses have limited knowledge about gender, identity and sexual orientation, although they know aspects of health policy and implement host actions in primary care services. Conclusion: there is a knowledge gap about the LGBTQIAP+ population among the surveyed nurses. It is evident the need to implement permanent education actions in order to train nurses in primary health care in the reception of this specific public.